Analisis Faktor Risiko Keluhan Muskuloskeletal pada Pandai Besi di Kecamatan Alak Kota Kupang - Mabilehi, Ansel Ronaldy Refael; Ruliati, Luh Putu; Berek, Noorce Christiani (Timorese Journal of Public Health, 2019)
Blacksmith are the job that produced sharp object like knife and choping knife. Worker doing with explanated by the factors that associated with musculoskeletal disorder. This research aim to know factors associated with musculoskeletal disorder in blacksmith in Alak Subdistrict Kupang City, 2018. This is an analytic research with Cross Sectional design. Population on this study amounted to 31 that used chi square analyze. This research doing at November 2018 in the three kelurahan that Kel. Alak, Kel. Nunbaun Sabu and Kel. Namosian with 31 worker and used total sampling. Dependent variable: Musculoskeletal Disorder. Independen variable: age, cumulation year of worked, time work per day, smoked habitual, work load, work posture, work temperature and noise.At this research, from 31 respondents be found 26% minor sigh, 39 % mild sigh dan 35% sever sigh. Staticsly associated variable are: cumulation of year worked (-Value 0,047), kerja, time work per day (p-Value 0,013), dan work posture (p-Value 0,031). Doesn’t associated variable: age (p-Value 0,457), smoked habit (p-Value 0,551), work load (p-Value 0,682), work temperature (p-Value 0,764) and noised (p-Value 0,302). Blacksmith must be better work posture and time of worked perday and hope so the other principal review variable that’s no researching at this research.